Efforts To Increase Activity And Learning Outcomes Of Job Application Letter Writing Skills Using The Inquiri Learning Model In Class XII MIPA 1 Students At MAN 1 Gunungkidul - Ris Mulyati Sholikhatul Muslikah (Journal of Social Science and Economics, 2023)
This research is about the application of learning using the Inquiry Learning model, increasing student learning achievement, and how active students are during the learning process. This research uses observation to determine the Inquiry Learning learning process, and to determine student activity, and tests to determine student learning outcomes. From the results of this research it was found that: (1) The learning process using the Inquiry Learning model is as follows: Stage 1: Conducive Atmosphere, Stage 2: Connect, Stage 3: Big Picture, Stage 4: Set Goals, Stage 5: Enter Information, Stage 6. Activation, Stage 7. Demonstrate, Stage 8. Review and Anchor (2) By applying the Inquiry Learning model, the learning outcomes of class first cycle and second cycle. The increase is as follows: In the initial condition, there were 69% of students who had not completed it, 31% of students who had completed it and 0% of students who had completed it. In the first cycle, there were 65.5% of students who had not completed it, 34.5% of students who had completed it and 0% of students who had completed it. In the second cycle, there were 0% of students who had not completed, 100% of students who had completed and 0% of students who had passed. Thus, until the second cycle, students whose learning results have completed reach 100%. (3) Students' motivation during the learning process of the first and second cycles increases, namely as follows: In the initial condition (a) students whose motivation is low is 25%, moderate motivation 70%, high motivation 5%. In the first cycle (a) 12% of students had low motivation, 69% had moderate motivation, 19% had high motivation. In the second cycle (a) students with low motivation were 8.89%, those with medium motivation were 56.22%, and those with high motivation were 34.89%.